Thermodynamic and Kinetic Study on the Reaction Mechanism of Paracetamol Formation from 4-Aminophenol Using Computational Chemistry Methods - Roma Sinaga; Julina Indah Gewa Sitompul; Asep Wahyu Nugraha (Universitas Negeri Medan, 2025)
Paracetamol, also known as acetaminophen, is one of the most widely used drugs worldwide and is included in the WHO Essential Medicines List. The synthesis process of paracetamol is carried out through the acetylation reaction of 4-aminophenol with acetic anhydride, producing paracetamol and acetic acid as a by-product. This study aims to analyze the thermodynamic and kinetic aspects of the paracetamol formation reaction from 4-aminophenol using a computational chemistry approach. Calculations were performed using the Restricted Hartree-Fock (RHF) method with a 3-21G basis set implemented in the NWChem software, while molecular structure visualization was conducted using Jmol and Avogadro. The results show that the energy change (ΔE) is –25.0107 kJ/mol (exothermic). In addition, the activation energy (Ea) required to reach the transition state is recorded at 623.13 kJ/mol.